Mind the gap: um estudo cross-cultural sobre atitude, intenção e comportamento de compra de produtos verdes - Ferraz, Sofia Batista (2012)
This research aims to analyze the relationships and the possible gap between attitude, intention and purchase behavior towards green products of Brazilian and Canadian management undergraduate students. This academic effort serves to contribute to the consolidation of the model proposed by Chan (2001), with the addition of situational factors such as availability, price and perceived quality suggested by Dinato and Madruga ( 1999), and Oppenheim Bonini (2008) and D'Souza et al. (2007). The research is quantitative and descriptive due to its objectives. This is a field study using the technique of Structural Equation Model (SEM). The results confirmed a positive relationship between attitude and intention to buy green products, as well as there is a positive relationship between intention and purchase behavior, though less expressive. The influence of availability, price and perceived quality between intention and purchase behavior was also confirmed. Regarding differences between the groups, it was found that Canadian students usually find green products more easily, and are more willing to spend money and better products abdicate in favor of the environment. Despite the differences between the samples, the perceived price is a dominant variable during the transition between intention and purchase behavior of green products, demonstrating general similarities between the two cultures. It is expected to contribute to the promotion of debates and discussions about the advantages and disadvantages in adopting green products, help Management educators seeking to evolve students curricula, stimulate new researches and assist in developing strategies in marketing based on the behavior of their consumers.